Performance analysis in material selection for surface insulation condition of high voltage application - Azhar, Sulaiman (2014)
High voltage insulation form an essential part of the high voltage electric power transmission systems. Any failure in the satisfactory performance of high voltage insulation can cause considerable loss of capital. The right material of insulator will perform optimization in production cost, maintenance cost and life time services. The performance of insulation materials can determine through the leakage current (LC) signal. That shows information of surface condition and pollution severity. Numerous of studies have been conducted to discover on insulation materials ageing in relation to surface condition, especially the correlation between LC harmonic components and deterioration of polymeric materials surface but still lack in analysis the performance of insulation materials specifically. This research presents the performance analysis of polymeric and non-polymeric insulation materials in contaminated condition using time frequency distribution (TFD). The selected materials are high density polyethylene, polypropylene and polystyrene as polymeric materials. Otherwise, glass is selected as a non-polymeric material. To demonstrate the performance of polymeric and non-polymeric insulation materials surface condition, LC signals is monitored and captured via non-standard inclined plane tracking (IPT) test. Then, the results are analyzed by using TFD which is spectrogram as a tool to diagnose and represent in time frequency representation (TFR). Parameters of signal are estimated from TFR to identify the LC signals patterns of the materials and to classify the surface condition via LC parameters. The findings of this research suggest that under contamination condition the insulating materials surface in certain voltage stress sustain several signals patterns as capacitive, resistive, symmetrical and unsymmetrical. The correlation between LC signal patterns and LC parameters is demonstrated the performance of insulating material surface conditions. Furthermore, this contribution can be applied for online monitoring and diagnosing erosion of insulation materials surface condition and it is very useful to the utility supplier. The conclusion can be drawn with approach of monitoring surface condition using TFD which is spectrogram is applied for analyze and demonstrate the performance of surface condition insulation materials.